Plant-Based Scaffolds Modify Cellular Response to Drug and Radiation Exposure Compared to Standard Cell Culture Models - Lacombe, Jerome; Harris, Ashlee F.; Zenhausern, Ryan; Karsunsky, Sophia; Zenhausern, Frederic (Frontiers in Bioengineering and Biotechnology, 2020)
Plant-based scaffolds present many advantages over a variety of biomaterials. Recent studies explored their potential to be repopulated with human cells and thus highlight a growing interest for their use in tissue engineering or for biomedical applications. However, it is still unclear if these in vitro plant-based scaffolds can modify cell phenotype or affect cellular response to external stimuli. Here, we report the characterization of the mechano-regulation of melanoma SK-MEL-28 and prostate PC3 cells seeded on decellularized spinach leaves scaffolds, compared to cells deposited on standard rigid cell culture substrate, as well as their response to drug and radiation treatment. The results showed that YAP/TAZ signaling was downregulated, cellular morphology altered and proliferation rate decreased when cells were cultured on leaf scaffold. Interestingly, cell culture on vegetal scaffold also affected cellular response to external stress. Thus, SK-MEL-28 cells phenotype is modified leading to a decrease in MITF activity and drug resistance, while PC3 cells showed altered gene expression and radiation response. These findings shed lights on the decellularization of vegetal materials to provide substrates that can be repopulated with human cells to better reproduce a soft tissue microenvironment. However, these complex scaffolds mediate changes in cell behavior and in order to exploit the capability of matching physical properties of the various plant scaffolds to diverse physiological functionalities of cells and human tissue constructs, additional studies are required to better characterize physical and biochemical cell-substrate interactions.